Two new dwarfgobies from the Indian and Western Pacific Oceans (Teleostei: Gobiidae: Eviota) - Greenfield, David W.; Jewett, Susan L. (Zootaxa, 2016)
Two new species of dwarfgobies are described, Eviota asymbasia from the Sulu Sea, Philippine Islands, south to Java and west to Damar, and E. bipunctata occurring from the Indian Ocean eastward into the western Pacific Ocean. Eviota asymbasia lacks the IT pore of the cephalic sensory-pore system and usually also the POP, has a dorsal/anal-fin formula of 8/8, has some pectoral-fin rays branched and usually 15 rays, two spots on the pectoral-fin base, no dark spot over the preural centrum, first dorsal fin may be filamentous, six ventral postanal spots, and the male genital papilla is not fimbriate. Eviota bipunctata belongs to the group with cephalic sensory-pore system pattern 2 (lacking only the IT pore), some pectoral-fin rays branched, pectoral-fin base with 1 or 2 prominent dark spots, dorsal/anal-fin formula usually 8/8, and no occipital spots.